Therapeutic activity and biodistribution of a nano-sized polymer-dexamethasone conjugate intended for the targeted treatment of rheumatoid arthritis - Rubanová, Daniela; Skoroplyas, Svitlana; Libánská, Alena; Randárová, Eva; Bryja, Josef; Chorvátová, Michaela; Etrych, Tomáš; Kubala, Lukáš (Nanomedicine, 2024)
Rheumatoid arthritis is a chronic inflammatory autoimmune disease caused by alteration of the immune system. Current therapies have several limitations and the use of nanomedicines represents a promising strategy to overcome them. By employing a mouse model of adjuvant induced arthritis, we aimed to evaluate the biodistribution and therapeutic effects of glucocorticoid dexamethasone conjugated to a nanocarrier based on biocompatible N-(2-hydroxypropyl) methacrylamide copolymers. We observed an increased accumulation of dexamethasone polymer nanomedicines in the arthritic mouse paw using non-invasive fluorescent in vivo imaging and confirmed it by the analysis of tissue homogenates. The dexamethasone conjugate exhibited a dose-dependent healing effect on arthritis and an improved therapeutic outcome compared to free dexamethasone. Particularly, significant reduction of accumulation of RA mediator RANKL was observed. Overall, our data suggest that the conjugation of dexamethasone to a polymer nanocarrier by means of stimuli-sensitive spacer is suitable strategy for improving rheumatoid arthritis therapy.
Keywords: dexamethason; Nanoparticles; RANKL; Arthritis, Rheumatoid; Drug Carriers; Biodistribution; tkáňová distribuce; zvířata; Rheumatoid arthritis; myši; Mice; polymery; revmatoidní artritida; Polymers; artritida experimentální; Dexamethasone; nanočástice; nosiče léků; Animals; HPMA; Tissue Distribution; Arthritis, Experimental